Новітні банківські продукти в Україні та передумови їх виникнення - Філоненко, Владислав Юрійович; Filonenko, Vladyslav Yuriyovych (Ірпінь, 2024)
Визначено сутність та складові банківських інновацій та їх впливу на банківську систему та економіку країни. Визначено підходи до класифікації банківських інновацій. Досліджено механізм розробки та впровадження нових банківських продуктів. Оцінка портфелю банківських продуктів комерційного банку. Розгляд особливостей впровадження нових продуктів у банку. Визначення перспектив вітчизняних комерційних банків щодо впровадження новітніх продуктів.

The essence and components of banking innovations and their influence are determined on the banking system and the country's economy. Approaches to the classification of banking innovations are defined. The mechanism of development and introduction of new banking products was studied. Evaluation of the portfolio of banking products of a commercial bank. Consideration of the peculiarities of the introduction of new products in the bank. Determination of the prospects of domestic commercial banks regarding the introduction of the latest products.
The latest banking products in Ukraine and the prerequisites for their development
Keywords: страховий ринок; страхові послуги; страхові компанії; Insur-технології; insurance market; insurance services; insurance companies; Insur-technologies